37 Thromboembolic events in left ventricular endocardial pacing: long-term outcomes from a multicentre uk registry. (5th June 2017) - Sawhney, Vinit; Domenichini, Guilia; Gamble, James; Furniss, Guy; Panagopoulos, Dimitrios; Haywood, Guy; Rajappan, Kim; Campbell, Niall; Lambiase, Pier; Sporton, Simon; Earley, Mark; Lowe, Martin; et al.
Abstract : Background: Endocardial left ventricular (LV) pacing is an effective alternative in patients with failed coronary sinus lead. However, the major concern is the unknown long-term thromboembolic risk and much of the data has come from a small number of centres. We examined the safety and efficacy of endocardial LV pacing across 4 UK centres, to determine the long-term thromboembolic risk. Methods and Results: Independent prospective registries from four UK centres were combied to include 68 consecutive patients from 2010–2015. Medical records were reviewed and patients were contacted for follow-up. Thromboembolic events were confirmed on imaging. Baseline patient demographics are shown in Table 1. 65% patients were already anticoagulated (39 AF, 1 DVT, 2 prosthetic valve, 2 previous LV thrombus). Mean CHADS2VASC2 score for the cohort was 3.5. 44% patients had trans-ventricular LV lead. The mean procedure and fluoroscopy times were 200±120 and 32±28 min. 75% had a silicone-insulated pacing lead. Post-procedure, three patients had haematomas and one had tamponade requiring pericardial drain. Functional improvement was noted with decrease in mean NYHA from 3.5±1 to 2.1±1.2 (p=0.001) and increase in LVEF from 26.5±12 to 34±18.1 (p=0.005) over a 20 month follow-up. Re-do procedure due to lead displacement was required in two patients. One patient underwent system extraction and surgical epicardial lead after device infection. The ischaemic stroke rate, defined as transient or permanent loss of function associated with imaging confirmation of a cerebral infarct in the appropriate territory, occurred in 4 patients (6%) providing an annual event rate of 3.6%. In multivariate analyses, the only significant correlation with the risk of CVA was sub-therapeutic INRs (p<0.01, CI 0.02–0.68, HR 0.12). There was no association between lead material and mode of delivery (transatrial/ventricular) and CVA. 14 patients died during follow-up with mean time to death post-procedure of 20 months. Cause of death was end-stage heart failure in all patients except three (pneumonia in two, knee sepsis). Conclusion: Endocardial LV lead in heart failure patients has a good success rate at 1.6 year follow-up. However, it is associated with a modest thromboembolic risk largely due to sub-therapeutic anticoagulation. These results have potential for improvement and newer oral anticoagulants might play a role in this setting.